ATTITUDES OF TEACHERS IN THE ARAB SCHOOLS IN ISRAEL TOWARDS INTEGRATION OF STUDENTS WITH SPECIAL NEEDS - Majadley, Enas (Rocznik Pedagogiczny, 2018)
The program for the integration of children with special needs in the regular educational frame- works supports and encourages the integration of children with a variety of special needs, tem- porary or ongoing, within the context of regular education, and sees integration as both a goal and value. The integration program is operated through a training and treatment system in the educational frameworks, which were formulated according to the special needs of those students. With the increase in the trend towards integration in Israel and the expectation that this trend will grow in the future, it is essential to continue to explore teachers’ perceptions and attitudes regarding integration as well as their needs for training and continuing education. The Arab education system in general and the issue of caring for children with special needs in school, in particular, are at huge gaps. The purpose of this paper is to review the literature on mainstream teachers’ at- titudes towards integration and, more recently, inclusion and to show the need of design research on attitudes of teachers in schools in Arab society in Israel towards the integration of students with special needs into regular classes.